Early adolescents’ visions of the future: towards hopeful and sustainable futures? - Corres, Andrea; Cebrián, Gisela; Junyent, Mercè (Frontiers in Education, 2024)
Education for Sustainable Development (ESD) particularly emphasises developing future-thinking competencies. Nevertheless, this line of thinking still represents a challenge for younger students, who tend to be left behind when deciding and visualising the future within educational spaces. Through a qualitative approach, our research attempts to explore early adolescents’ views concerning probable and preferable futures and how they are related to sustainable development dimensions. For this purpose, we asked 352 students in the fifth and sixth grades of primary schools in the province of Tarragona (Spain) to explain their visions regarding the probable and preferable futures of their city or town. We analysed the data through an inductive-deductive approach. Our findings indicate that the students’ pessimistic visions of the future require a special effort from an ESD viewpoint to educate them towards hopeful futures. Different degrees of complexity in their views of the futures were identified in relation to sustainability, denoting the need to design diagnostic tools that properly guide pedagogical approaches and interventions towards developing sustainability competencies.